Psychological distress and anxiety compared amongst dental patients- results of a cross-sectional study in 1549 adults - Alexander Zinke; Christian Hannig; Hendrik Berth (BMC, 2019)
Abstract Background This study aimed to identify anxiety in dental patients visiting a dental clinic using the Dental Anxiety Scale, their level of psychological distress using the Brief Symptom Inventory-18 and therefore identifying a correlation between these groups as well as their gender and age. Methods An adult sample of N = 1549 patients (865 females, 779 males) was examined over the course of three years using the Brief Symptom Inventory-18 to evaluate psychological distress and the Dental Anxiety Scale to determine anxiety before dental treatment. Evaluations were conducted according to age and gender. Results There was no correlation between different age groups of the sample the Dental Anxiety Scale. Anxiety, depression and GSI were more frequent in patients below the age of 46 than above. Women were more susceptible to signs of Anxiety and Somatization and scored higher on the Dental Anxiety Scale and the Global Severity Index than male patients. There was a significant positive correlation between scores of the BSI-18 categories: Somatization, Anxiety and Depression and the DAS for dental patients. Conclusions This study showed that a relationship between dental anxiety and psychological distress exists. It would be an improvement to use a short questionnaire like the Dental Anxiety Scale to evaluate a patient before his first treatment so that more appropriate treatments can be pursued.